Evaluation of Multimedia User Interface Design Method for M-learning (MobLearn): A Comparative Study (Informatica, 2021)
The multimedia m-learning method (MobLearn method) is a holistic and functional method that includes the key steps, methods, and techniques for using multimedia to create m-learning interfaces. In this paper, the MobLearn process was evaluated by comparing it to one of the latest m-learning methods by Stanton and Ophoff (2013( that has the same function. The comparative case study was employed to examine the degree to which two m-learning approaches are similar in terms of interface architecture and their main characteristics, their differences and the primary function of features that occur in one of them but not in the other. Based on this comparative study, the final version of MobLearn method has been introduced in two forms: high-level framework and method steps. In this version, the mapping strategies of m-learning have been applied where the mapping techniques deal with a different set of information types and a large variety of media.